Catalog of taxa introduced by Luitfried Salvini-Plawen (1939–2014) - Affenzeller, Susanne; Steiner, Gerhard (Zootaxa, 2017)
Luitfried Salvini-Plawen was one of the most distinguished researchers for molluscan phylogenetic systematics of the last decades. In his publications he described a total of 193 species: 134 Solenogastres, 34 Caudofoveata, 14 interstitial Gastropoda, one polyplacophoran and the remaining comprising Cnidaria, Priapulida, Kamptozoa, and Echinodermata. In addition, he introduced 47 genus-group names and 54 names for family-level and higher taxa. This catalog comprises lists of all taxon names published by Luitfried Salvini-Plawen. The catalog entries contain taxonomic information, original citations, type localities and type collections. It aims to facilitate further research on these and related taxa.